PEMBERDAYAAN MASYARAKAT SEBAGAI KAMPUNG TEMATIK DESA GUNUNG MALANG KECAMATAN TENJOLAYA KABUPATEN BOGOR - Syaiful Syaiful; Ali Taufikfajar; Larasati Ayu Pramesti (PKM Maju UDA, 2021)
Improvements in the program delivered are the program for a healthy house using building materials, components of spatial planning, lighting, air quality and ventilation. Likewise with the provision of clean water, disease vectors, waste disposal and residential density. The average level of occupancy density in Gunung Malang village is still low, so it is very possible that there will be healthy houses, but the quality of the buildings is an obstacle. The approach methods used in this healthy home counseling program are: (1) a religious approach in prayer rooms and mosques as well as recitations; (2) kinship approach; (3) Social approach. The result of this counseling that can be achieved for the community is the increase in community knowledge in managing healthy and livable homes. Counseling comes from the word "suluh" which means "torch" or "lamp" or "that gives light". With counseling, it is hoped that there will be an increase in knowledge, skills and attitudes. Counseling is a process of changing behavior among the community so that they know, are willing and able to make changes in order to achieve increased production, income/profits and improvement of their welfare.